2013
DOI: 10.1093/chemse/bjt021
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Taste Sensitivity in Congenital Blindness

Abstract: Sight is undoubtedly not only important for food identification and selection but also for the modulation of gustatory sensitivity. We can, therefore, assume that taste sensitivity and eating habits are affected by visual deprivation from birth. We measured taste detection and identification thresholds of the 5 basic tastants in 13 congenitally blind and 13 sighted control subjects. Participants also answered several eating habits questionnaires, including the Food Neophobia Scale, the Food Variety Seeking Ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 55 publications
2
32
2
Order By: Relevance
“…2C and 2D. Our group further demonstrated that congenitally blind subjects have a better intuitive eating at titude (Tylka, 2006) compared to sighted subjects (Gagnon et al, 2013), a finding that was replicated by compiling data from our Danish and Canadian samples (Fig. IB).…”
Section: Behavioural Studiessupporting
confidence: 70%
See 3 more Smart Citations
“…2C and 2D. Our group further demonstrated that congenitally blind subjects have a better intuitive eating at titude (Tylka, 2006) compared to sighted subjects (Gagnon et al, 2013), a finding that was replicated by compiling data from our Danish and Canadian samples (Fig. IB).…”
Section: Behavioural Studiessupporting
confidence: 70%
“…Importantly, we have shown that taste sensitivity is lowered in congenital blindness (Gagnon et al, 2013), mak ing gustation the only remaining sensory modality in which the blind do not outperform the sighted. Indeed, taste detection and identification thresholds are significantly elevated in congenitally blind subjects compared to blind folded sighted controls, as illustrated in Fig.…”
Section: Behavioural Studiesmentioning
confidence: 81%
See 2 more Smart Citations
“…Sighted controls in this case show the same lateralized right-olfactory and left-verbal pattern but all over their brain with no or little occipital activations (Renier et al, 2013). Fewer studies explored taste differences between blind and sighted and recent results show increased thresholds in taste detection and identification in the blind (Gagnon et al, 2013). …”
Section: Odor and Tastementioning
confidence: 99%